Effect of Price Earning Ratio, Earning Per Share, Projected Earning Growth, and Dividend Policy on stock prices of property and real estate sector companies listed on the Indonesian Stock Exchange in 2018-2022 - Natalia, Ivane; Nurdiana, Diah (PT. Riset Press International, 2024)
This study's overarching goal is to quantify the impact on stock price of several financial variables such as price earnings ratio, earnings per share, projected earning growth, and dividend policy. Companies in the real estate and property industry that were listed on the Indonesia Stock Exchange between 2018 and 2022 make up the population of this study. To get a representative sample of seven businesses, use the purposive sampling technique. This is a study of deep data analysis approaches that use SPSS 26's multiple linear regression analysis. The research found that the price earnings ratio has a positive and statistically significant effect on stock prices, earnings per share has a positive and statistically significant effect on stock prices as well, projected earnings growth has a negative and statistically significant effect on stock prices, dividend policies has a negative and statistically insignificant effect, and all four of these factors have a positive and statistically significant effect on stock prices when taken together.